VISUALISASI KORBAN TALAK DALAM LUKISAN GAYA SURREALIS - Ir. Drs. Heldi, M.Si., Ph.D., GUSRIANDI, Drs. Idran Wakidi, (Serupa The Journal of Art Education, 2017)
This thesis aims to visualize the condition of divorce in a surrealist painting, to increase people's appreciation of the importance of keeping the family intact. Embodiments of surrealist painting dominating form elements, atmosphere and expression between the subject mater to support the object through the medium of acrylic on canvas in the style surrealism. Methods and steps in the process begins with the preparation, elaboration, synthesis, the realization the concept going to presented to public through exhibitions. This work provides information to the general public picture of viewpoints contained in the phenomenon of divorce or divorce as a social standpoint, law and religion are illustrated through 10 (ten) title surrealist painting style.Kata Kunci: Korban Talak, Seni Lukis, Surrealis